Restorative Justice-Based Criminal Justice System: Integration of Victim Trust Funds in the Criminal Code Procedure - Kusumawati, Apriliani (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2025)
The concept of restorative justice in the criminal justice system places the victim as the main subject who has the right to receive compensation for the suffering experienced, including the right to compensation. However, in practice, the applicable regulations, such as the Code of Criminal Procedure and Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning the Protection of Witnesses and Victims, still show weakness in accommodating the rights of victims comprehensively. Victim Trust Fund, as regulated in Law Number 12 of 2022 on the Crime of Sexual Violence, along with its implementing regulations, is an important instrument to guarantee the fulfillment of victims' rights to compensation and other forms of recovery. The main issue discussed in this article is the position of the Victim Trust Fund in the right to recovery framework for victims and how the urgency of the integration of the Victim Trust Fund in the Code of Criminal Procedure as an Effort to Realise Restorative Justice.